1999
DOI: 10.1093/ije/28.3.532
|View full text |Cite
|
Sign up to set email alerts
|

Growth of children according to maternal and child HIV, immunological and disease characteristics: a prospective cohort study in Kinshasa, Democratic Republic of Congo

Abstract: The HIV-infected children in Congo with no access to antiretroviral therapy were stunted, underweight, and wasted compared to same age uninfected children. Both HIV infection and HIV-associated signs and symptoms, not maternal immunological or socioeconomic circumstances, placed children at risk for growth retardation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
103
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 29 publications
12
103
2
2
Order By: Relevance
“…However, the role of HIV exposure during pregnancy, delivery and breastfeeding on postnatal growth remains uncertain. Previous to availability of antiretroviral drugs, several studies showed poor growth outcomes in HEU children compared with HIVunexposed children [41,42]. However, reports in which antiretroviral drugs for PMTCT were used either found no differences in growth outcomes between HEU and HIV-unexposed children or if they existed were most likely due to different feeding practices rather than to HIV exposure [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of HIV exposure during pregnancy, delivery and breastfeeding on postnatal growth remains uncertain. Previous to availability of antiretroviral drugs, several studies showed poor growth outcomes in HEU children compared with HIVunexposed children [41,42]. However, reports in which antiretroviral drugs for PMTCT were used either found no differences in growth outcomes between HEU and HIV-unexposed children or if they existed were most likely due to different feeding practices rather than to HIV exposure [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that women with secondary education are better informed about optimal child care practices [8], have better practices in terms of hygiene [27,28], feeding [18] and childcare during illness [18,21,22], have a greater ability to use the health system [29], are more empowered to make decisions [28] and are more likely to have financial resources to care for and feed children [18]. There has been a slight increase in the percentage of women who have completed secondary education in Rwanda, from 1.2 % in 2005 [30] to 2.8 % in 2010 [10], and we hypothesize that further gains in women's education may translate into improved child nutrition outcomes [7,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…2 HIV-infected children tend to weigh less than uninfected children at birth, and they continue to lag behind uninfected children of similar age in weight and especially height. [3][4][5][6][7][8][9][10][11][12] Previous reports of growth among HIV-infected children receiving HAART had mixed results. A cohort analysis of 906 children showed small but statistically significant improvements in height and weight growth (adjusted for age and gender) after children began receiving PIs.…”
mentioning
confidence: 99%